Pengaruh Digital Marketing Dan Brand Loyalty Terhadap Keputusan Pembelian Pada Konsumen @Scarlett_Whitening Di Instagram - Refah Raslina Zahra; Eman Sulaeman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to ascertain whether or not brand loyalty and digital marketing influence purchasing decisions simultaneously. The approach taken in this research method is quantitative. Through the use of the Google form link, questionnaires were distributed in order to collect the data used in this study. A purposive sampling strategy was used to collect samples from 110 @Scarlett_Whitening customers in Malang City. The hypothesis was tested using the t test (partial), the F test (simultaneous), and the determination test (R2) in the multiple linear regression analysis method. Digital marketing has a significant positive impact on @Scarlett_Whitening's purchasing decisions, and brand loyalty has a significant positive impact as well, according to some of the study's findings. Digital marketing and brand loyalty have a significant positive impact on @Scarlett_Whitening's purchasing decisions, according to the study's findings simultaneously.